Transcriptionally Active High-Risk Human Papillomavirus is Not a Common Etiologic Agent in the Malignant Transformation of Inverted Schneiderian Papillomas - Rooper, Lisa M. (Head Neck Pathol, 2017)
The role of human papillomavirus (HPV) as an etiologic and transformational agent in inverted Schneiderian papilloma (ISP) is unclear. Indeed, reported detection rates of HPV in ISPs range from 0 to 100%. The true incidence has been confounded by a tendency to conflate high- and low-risk HPV types and by the inability to discern biologically relevant from irrelevant HPV infections. The recent development of RNA in situ hybridization for high-risk HPV E6/E7 mRNA now allows the direct visualization of transcriptionally active high-risk HPV in ISP, providing an opportunity to more definitively assess its role in the development and progression of ISPs. We performed p16 immunohistochemistry and high-risk HPV RNA in situ hybridization on 30 benign ISPs, 7 ISPs with dysplasia, 16 ISPs with carcinomatous transformation, and 7 non-keratinizing squamous cell carcinomas (SCCs) with inverted growth that were unassociated with ISP. Transcriptionally active HPV was not detected in any of the 52 ISPs including those that had undergone carcinomatous transformation, but it was detected in two of seven (29%) non-keratinizing SCCs that showed inverted growth. There was a strong correlation between high-risk HPV RNA in situ hybridization and p16 immunohistochemistry (97%; p < 0.01). These results indicate that transcriptionally active high-risk HPV does not play a common role in either the development of ISP or in its transformation into carcinoma.